Quality assessment of milk in supply chain of Parbhani sub-division - chappalwar, Anita; Jawale, Manisha; Devangare, Ashok (Indian Journal of Dairy Science, 2022)
Present study was aimed to detect common adulterants and physico-chemical properties of milk samples collected from different levels viz. farmer/vendors, collection centre (CC) and milk processing plants (Govt./Co-operative dairy) in Parbhani sub-division (Parbhani, Gangakhed, Jintur, Selu, Purna and Palam taluka). During the study minimum and maximum values for water, total solids (TS), fat, solid not fat (SNF), protein and lactose content 79.05%, 10.90% .3.43%, 5.36%, 2.57%, 3.47% 88.88%,12.15%, 11.18%, 9.17%, 4.01%, 5.36% were observed for in the milk samples of Parbhani sub division. Statistical analysis revealed significant difference (P<0.05) in water, fat, protein content, % acidity of milk samples collected from different levels and non significant difference in TS, SNF, lactose content, pH value of milk samples collected from different levels of Parbhani subdivision. However density of milk samples did not differed significantly among both different levels as well as taluka. Most of the compositional parameters were found below the FSSAI standards for buffalo milk. More or less amount of extraneous water was added in all the milk samples of Parbhani subdivision. Adulterants viz, detergents, skim milk powder (SMP), sucrose, nitrate and urea was detected in vendor™s milk samples. None of the adulterant was detected in dairy of Parbhani subdivision; however CC milk samples of Jintur and Purna taluka were only positive for presence of detergent. From the study, it is concluded that adulteration of milk is a generally practiced by vendors which results in the deterioration of nutritive and microbiological quality of milk.